Ionic liquid-based sample pretreatment platforms: comparing solid supports and aqueous biphasic systems for enhanced bioanalytical performance - Maria S.M. Mendes; Hugo Santos; Inês Cruz; Márcia C. Neves; Mara G. Freire; Francisca A. e Silva (Sustainable Chemistry and Pharmacy, 2026)

A Ride in Semi-arid: Evaluation of Remote Sensing-based Indices for the Detection and Monitoring of Surface Water Bodies Under Dry and Wet Periods - Eduardo Gonçalves Patriota; Guillaume Francis Bertrand; Alexandro Medeiros Silva; Natalia Maria Mendes da Silva; Khalil Grisi Velôso Mendes; José Welton Gonçalo de Sousa; Richarde Marques da Silva; Cristiano das Neves Almeida; Cinthia Maria de Abreu Claudino; Carolyne Wanessa Lins de Andrade Farias; Jorge Flávio C. B. C. Silva; Victor Hugo Rabelo Coelho (Water Resources Management, 2026)

Retraction notice to ‘Aluminum: A potentially toxic metal with dose-dependent effects on cardiac bioaccumulation, mineral distribution, DNA oxidation and microstructural remodeling’ [Environ. Pollut. 242, Part A (2018) 814-826] - Rômulo D. Novaes; Viviane G.S. Mouro; Reggiani V. Gonçalves; Andrea A.S. Mendonça; Eliziária C. Santos; Maria C.Q. Fialho; Mariana Machado-Neves (Environmental Pollution, 2026)

Quantifying leaf herbivory: A guide to methodological trade‐offs and best practices - Tatiana Cornelissen; Gisele M. Mendes; Fernando A. O. Silveira; Wesley Dáttilo; Roger Guevara; Ramiro Aguilar; Maria Gabriela Boaventura; Ricardo Campos; Ek del Val; Guilherme Ramos Demetrio; Marcilio Fagundes; Rafael de Paiva Farias; et al. (Ecology, 2026)
Leaf herbivory is a ubiquitous ecological interaction that varies significantly in intensity across species, habitats, and biogeographic regions. Although quantification of leaf damage is crucial for understanding many ecological processes, the accuracy and precision of various damage estimation methods used by researchers, including visual estimation, digital image analysis, and artificial intelligence, have not been evaluated and compared. We use a phylogenetically diverse group of tropical plants to compare the accuracy and precision of damage estimation methods and use the results to provide a guide to herbivory estimation that balances the advantages and disadvantages of each method. We found that visual estimation tended to overestimate herbivory levels compared to digital methods but was 15 times faster and improved in accuracy and speed with training. Conversely, deep‐learning algorithms underestimated herbivory relative to image analysis with ImageJ when it was on the margin, but showed similar accuracy for damage inside of leaf margins. Our results indicate that while visual methods allow for rapid assessment of large sample sizes and are suitable for detecting broad patterns of damage, image analysis is crucial for accurate and precise quantification. The disadvantages of each method, however, can be minimized through proper training and efficient use of each tool, and we therefore provide a guide of practical approaches to herbivory estimation.

Immobilization of laccase on grape seed-derived hydrochar and biochar as sustainable biocatalysts for efficient pharmaceutical degradation in real wastewater - Helena Sá; Michele Michelin; Teresa Tavares; Maria Angeles Sanroman; Emilio Rosales; Isabel C. Neves; Bruna Silva (Journal of Environmental Chemical Engineering, 2025)

A critical analysis of the marina environmental risk assessment method applied to Portugal - Maria C. Neves; Alexandra Cravo; José Jacob; Catia Correia (Regional Studies in Marine Science, 2025)

Acid-modified titanate nanotubes for enhanced photocatalytic removal of contaminants of emerging concern in water - Guenther Carlos C. Viana; Djalma L.S. Maia; Daniel A.S. Rodrigues; Lara Fabian S. Ribeiro; Italo O. Mazali; Fernando Rodrigues-Silva; Maria Clara V.M. Starling; Thiago A. Neves; Camila C. Amorim (Journal of Water Process Engineering, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Tackling water contamination by oncologic drugs: Supported ionic liquids as sustainable adsorbents for cyclophosphamide removal - Rafael Francisco; Bruna Monteiro; Maria J. Santos; Francisca A. e Silva; Catia Venancio; Marcia C. Neves; Isabel Lopes; Ana C.A. Sousa; Mara G. Freire (Journal of Environmental Management, 2024)

Patterns and trends of atmospheric mercury in the GMOS network: Insights based on a decade of measurements - Mariantonia Bencardino; Francesco D’Amore; Hélène Angot; Lorenzo Angiuli; Yann Bertrand; Warren Cairns; María C. Diéguez; Aurélien Dommergue; Ralf Ebinghaus; Giulio Esposito; Kateřina Komínková; Casper Labuschagne; et al. (Environmental Pollution, 2024)

Integrating standardized indices and performance indicators for better drought assessment in semi-arid coastal aquifers - Maria C. Neves (Groundwater for Sustainable Development, 2024)

Evidence of plastics contamination and sewage-derived residues in a Brazilian Hope Spot for conservation of marine biodiversity - Cagarras Islands and surrounding waters - Raquel A.F. Neves; Nathália Rodrigues; Guilherme de Luca; Maria Alene A. Oliveira; Thuany F. Carvalho; Nicole S. Santos; Maria Eduarda S. Adelino; Luiza Belli Caldas; Agatha Miralha; Clarissa Naveira; Antonio J.S. Rodrigues; Igor C. Miyahira; et al. (Marine Pollution Bulletin, 2024)

Spatiotemporal distribution of invertebrate fauna in a mesovoid shallow substratum in iron formations - Lígia Maria Saback Moreira Dornellas; Pedro Giovâni da Silva; Maria Elina Bichuette; Augusto S. Auler; David C. Culver; Tanja Pipan; Lorena Oliveira Pires; Frederico de Siqueira Neves (Biodiversity and Conservation, 2024)

Antimicrobial Resistance Profiles of Multidrug-Resistant Enterobacteria Isolated from Feces of Weaned Piglets - Marlon do Valle Barroso; Juliana Soares da Silva; Sofia Magalhães Moreira; Yasmin Neves Vieira Sabino; Gabriel Cipriano Rocha; Maria Aparecida Scatamburlo Moreira; Denise Mara Soares Bazzolli; Hilario C. Mantovani (Current Microbiology, 2024)

A new Loriciferan, Scaberiloricus samba gen. et sp. nov., links the Higgins larva and the aberrant Shira larva - Martin V. Sørensen; Maria Herranz; Ricardo C. Neves; Reinhardt M. Kristensen; André R. S. Garraffoni (Organisms Diversity & Evolution, 2023)
A new genus and species of Loricifera, Scaberiloricus samba gen. et sp. nov., is described from the continental shelf and slope off Rio de Janeiro, Brazil. Adult morphology remains unknown for the new entity, but information is available from three different Higgins larval instars. The Higgins larva of the new species is characterised by a bulbous head and a slender, elongate trunk, separated by a constriction behind the head. The cuticle of the thorax and the posterior part of the head is characterised by numerous longitudinal zigzag folds. The new species and genus shows greatest morphological resemblance with Wataloricus japonicus , and a phylogenetic analysis based on Higgins larval morphological characters suggests that Scaberiloricus gen. nov., Wataloricus , Tenuiloricus , and Patuloricus form a monophyletic group within Pliciloricidae. The analysis furthermore suggests that the Higgins larvae of Scaberiloricus gen. nov. and Wataloricus represent transitional, evolutionary stages towards the highly aberrant Shira larvae, found in species of Tenuiloricus and Patuloricus .

1,4-Diaryl-1,2,3-triazole neolignan–celecoxib hybrids inhibit experimental arthritis induced by zymosan - Josyelen L. Felipe; Iluska S. Bonfá; Paloma K. M. B. Lossavaro; Joyce S. Lencina; Diego B. Carvalho; Luciane Candeloro; Giovanni I. S. Ferreira; Amarith R. das Neves; Maria Inês L. Souza; Saulo E. Silva-Filho; Adriano C. M. Baroni; Mônica C. Toffoli-Kadri (Inflammopharmacology, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

The signature of NAO and EA climate patterns on the vertical structure of the Canary Current upwelling system - Tina Georg; Maria C. Neves; Paulo Relvas (Ocean Science, 2023)
The current study aims to analyse the vertical structure of the ocean during upwelling events using in situ and modelled data. Additionally, the influence of climate patterns, namely the North Atlantic Oscillation (NAO) and the East Atlantic (EA) pattern, on the vertical structure and their impact on the upwelling activity are assessed for a period of 25 years (1993–2017). The study focuses on the central part of the Canary Current (25–35∘ N) with persistent upwelling throughout the year, with an annual cycle and the strongest events from June to September. Upwelling is determined using two different approaches: one index is calculated based on temperature differences between the coastal and the offshore area, and the other is calculated based on wind data and the resulting Ekman transport. Different datasets were chosen according to the indices. Stable coastal upwelling can be observed in the study area for the analysed time span, with differences throughout the latitudes. A deepening of the isothermal layer depth and a cooling of temperatures are observed in the vertical structure of coastal waters, representing a deeper mixing of the ocean and the rise of cooler, denser water towards the surface. During years of a positive NAO, corresponding to a strengthening of the Azores High and the Icelandic Low, stronger winds lead to an intensification of the upwelling activity, an enhanced mixing of the upper ocean, and a deeper (shallower) isothermal layer along the coast (offshore). The opposite is observed in years of negative NAO. Both effects are enhanced in years with a coupled, opposite phase of the EA pattern and are mainly visible during winter months, where the effect of both indices is the greatest. The study therefore suggests that upwelling activities are stronger in winters of positive North Atlantic Oscillation coupled with a negative East Atlantic pattern and emphasizes the importance of interactions between the climate patterns and upwelling.

Evidence of earthquake seasonality in the Azores Triple Junction - Ana L. Lordi; Maria C. Neves; Susana Custódio; Stéphanie Dumont (Geo-Marine Letters, 2023)
This work presents evidence of seasonal and inter-annual variations of the earthquake occurrence rate in the Azores Triple Junction, on the Mid-Atlantic Ridge (MAR). Annual cycles in microearthquakes are relatively common in intraplate continental regions affected by large hydrological loads, but this is the first time that earthquake seasonality is recognized near mid-ocean ridges. First, we benchmark the methodology by matching the published results of earthquake seasonality in the intraplate New Madrid Seismic Zone (USA). Next, we analyze the Azores earthquake catalogue, from 2008 to 2018, separately for oceanic and island regions. The results demonstrate that the seasonal modulation of the seismicity rate is only observed in the ocean, especially in the vicinity of the triple junction, with more earthquakes occurring during the summer months from May to August. Monte Carlo simulations show that the probability of observing such seasonality by chance is less than 1% for the magnitude band from 3.3 to 4.5, well above the detection threshold and magnitude of completeness of the seismic catalogue. The methodology includes a Jack-Knife approach, which shows that the oceanic seasonality is not the consequence of abnormal or extreme events. Although we speculate about possible earthquake triggering processes, it remains a challenge to definitely establish the mechanism responsible for the observed earthquake seasonal modulation in the Azores.

Granulated biomass fly ash coupled with fenton process for pulp and paper wastewater treatment - João Peres Ribeiro; Nuno C. Cruz; Márcia C. Neves; Sónia M. Rodrigues; Luís A.C. Tarelho; Maria Isabel Nunes (Environmental Pollution, 2023)

Numerical Model of Constrained Wave Energy Hyperbaric Converter under Full-Scale Sea Wave Conditions - Moisés Brito; Francisco Bernardo; Maria G. Neves; Diogo R. C. B. Neves; Alejandro J. C. Crespo; José M. Domínguez (Journal of Marine Science and Engineering, 2022)
A 2D numerical investigation of the power absorption of a constrained wave energy hyperbaric converter (WEHC) under full-scale sea wave conditions is presented. A fully non-linear numerical model DualSPHysics, based on the coupling of a smoothed particle hydrodynamics (SPH) fluid solver with a multibody dynamics solver, is used to model the interaction between wave and WEHC sub-systems. The numerical model was first validated against experimental data for a similar device, with a good accordance between PTO position and velocity. The model is then employed to study the hydrodynamics of a constrained WEHC considering several sea states, different hydraulic power take-off (PTO) damping and breakwater geometries. It is observed that the capture width ratio (CWR) is particularly sensitive to variations in the PTO damping, although the CWR absolute maximum is less sensitive considering mild variations applied to the PTO damping. Both wave height and wave period have an important effect on the CWR. The breakwater geometry is also essential for the performance of the WEHC, with a decrease in maximum CWR of about 15% for porous breakwater. These results are necessary to understand the full-scale behaviour of WEHC.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Groundwater response to climate variability in Mediterranean type climate zones with comparisons of California (USA) and Portugal - Katherine A. Malmgren; Maria C. Neves; Jason J. Gurdak; Luis Costa; José P. Monteiro (Hydrogeology Journal, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

How much leaf area do insects eat? A data set of insect herbivory sampled globally with a standardized protocol - Gisele M. Mendes; Fernando A. O. Silveira; Carolina Oliveira; Wesley Dáttilo; Roger Guevara; Betsabé Ruiz‐Guerra; Maria Gabriela Boaventura; Sershen; Syd Ramdhani; Shyam S. Phartyal; Sérvio P. Ribeiro; Victor Diniz Pinto; et al. (Ecology, 2021)
Herbivory is ubiquitous. Despite being a potential driver of plant distribution and performance, herbivory remains largely undocumented. Some early attempts have been made to review, globally, how much leaf area is removed through insect feeding. Kozlov et al., in one of the most comprehensive reviews regarding global patterns of herbivory, have compiled published studies regarding foliar removal and sampled data on global herbivory levels using a standardized protocol. However, in the review by Kozlov et al., only 15 sampling sites, comprising 33 plant species, were evaluated in tropical areas around the globe. In Brazil, which ranks first in terms of plant biodiversity, with a total of 46,097 species, almost half (43%) being endemic, a single data point was sampled, covering only two plant species. In an attempt to increase knowledge regarding herbivory in tropical plant species and to provide the raw data needed to test general hypotheses related to plant–herbivore interactions across large spatial scales, we proposed a joint, collaborative network to evaluate tropical herbivory. This network allowed us to update and expand the data on insect herbivory in tropical and temperate plant species. Our data set, collected with a standardized protocol, covers 45 sampling sites from nine countries and includes leaf herbivory measurements of 57,239 leaves from 209 species of vascular plants belonging to 65 families from tropical and temperate regions. They expand previous data sets by including a total of 32 sampling sites from tropical areas around the globe, comprising 152 species, 146 of them being sampled in Brazil. For temperate areas, it includes 13 sampling sites, comprising 59 species. Thus, when compared to the most recent comprehensive review of insect herbivory (Kozlov et al.), our data set has increased the base of available data for the tropical plants more than 460% (from 33 to 152 species) and the Brazilian sampling was increased 7,300% (from 2 to 146 species). Data on precise levels of herbivory are presented for more than 57,000 leaves worldwide. There are no copyright restrictions. Please cite this paper when using the current data in publications; the authors request to be informed how the data is used in the publications.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The Azores: A Mid-Atlantic Hotspot for Marine Megafauna Research and Conservation - Pedro Afonso; Jorge Fontes; Eva Giacomello; Maria C. Magalhães; Helen R. Martins; Telmo Morato; Verónica Neves; Rui Prieto; Ricardo S. Santos; Mónica A. Silva; Frédèric Vandeperre (Frontiers in Marine Science, 2020)

Large Aortic Prosthesis Fungal Vegetation Due to Candida parapsilosis: An Uncommon Presentation - Melyna C. Leite-Andrade; Cicero P. Inácio; Fernanda Calixto; Marcela Feitosa; Diana P. L. Sepulveda; Franz A. G. Santos; Maria Daniela S. Buonafina; Reginaldo G. Lima-Neto; Rejane P. Neves (Mycopathologia, 2019)

The impact of atmospheric teleconnections on the coastal aquifers of Ria Formosa (Algarve, Portugal) - Maria C. Neves; Luis Costa; Rui Hugman; José P. Monteiro (Hydrogeology Journal, 2019)

Are Trechisporales ectomycorrhizal or non-mycorrhizal root endophytes? - Mary Luz Vanegas-León; Marcelo A. Sulzbacher; Andrea C. Rinaldi; Mélanie Roy; Marc-André Selosse; Maria Alice Neves (Mycological Progress, 2019)

Sustained mass coral bleaching (2016–2017) in Brazilian turbid-zone reefs: taxonomic, cross-shelf and habitat-related trends - Carolina D. Teixeira; Rodrigo L. L. Leitão; Felipe V. Ribeiro; Fernando C. Moraes; Leonardo M. Neves; Alex C. Bastos; Guilherme H. Pereira-Filho; Milton Kampel; Paulo S. Salomon; João A. Sá; Ludmilla N. Falsarella; Michelle Amario; et al. (Coral Reefs, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Increasing levels of supplementation for crossbred steers on pasture during the dry period of the year - Daniele Soares Barroso Neves; Robério Rodrigues Silva; Fabiano Ferreira da Silva; Laize Vieira Santos; George Abreu Filho; Sinvaldo Oliveira de Souza; Marceliana da C. Santos; Weder Jansen Rocha; Ana Paula Gomes da Silva; Mateus de Melo Lisboa; Maria Magna Silva Pereira; Venício Macedo Carvalho (Tropical Animal Health and Production, 2018)

Scleroderma meridionale ectomycorrhizae on Halimium halimifolium: expanding the Mediterranean symbiotic repertoire - Marco Leonardi; Maria-Alice Neves; Ornella Comandini; Andrea C. Rinaldi (Symbiosis, 2018)

The Inventory of Geological Heritage of the State of São Paulo, Brazil: Methodological Basis, Results and Perspectives - Maria da Glória Motta Garcia; José Brilha; Flávia Fernanda de Lima; Jean Carlos Vargas; Annabel Pérez-Aguilar; Adriana Alves; Ginaldo Ademar da Cruz Campanha; Wânia Duleba; Frederico Meira Faleiros; Luiz Alberto Fernandes; Marisa de Souto Matos Fierz; Maria Judite Garcia; et al. (Geoheritage, 2018)

The expression patterns of aquaporin 9, vacuolar H+-ATPase, and cytokeratin 5 in the epididymis of the common vampire bat - Mariana M. Castro; Bongki Kim; Eric Hill; Maria C. Q. Fialho; Luciano C. H. P. Puga; Mariella B. Freitas; Sylvie Breton; Mariana Machado-Neves (Histochemistry and Cell Biology, 2017)

Differential Impact of Acclimation and Acute Water Deprivation in the Expression of Key Transcription Factors in Soybean Roots - Fábia Guimarães-Dias; Anna C. Neves-Borges; Alessandra J. Conforte; Leonardo Giovanella-Kampmann; André V. J. Ferreira; Regina M. S. Amorim; Magda A. Benevent; Maria Eugênia Lisei de Sá; Rosilene O. Mesquita; Fabiana A. Rodrigues; Alexandre L. Nepomuceno; Eduardo Romano; et al. (Plant Molecular Biology Reporter, 2016)

Climatic and geologic controls on the piezometry of the Querença-Silves karst aquifer, Algarve (Portugal) - Maria C. Neves; Luis Costa; José P. Monteiro (Hydrogeology Journal, 2016)

First account on kinorhynchs from Portugal, with the description of two new species: Echinoderes lusitanicus sp. nov. and E. reicherti sp. nov. - Ricardo C. Neves; Martin V. Sørensen; Maria Herranz (Marine Biology Research, 2016)

Neonatal Candidemia Caused by Candida haemulonii: Case Report and Review of Literature - Carolina M. Silva; Ana M. R. Carvalho-Parahym; Danielle P. C. Macêdo; Reginaldo G. Lima-Neto; Elaine C. Francisco; Analy S. A. Melo; Maria da Conceição M. Silva; Moacir B. Jucá; Luciana R. B. Mello; Rosemary M. J. Amorim; Rejane P. Neves (Mycopathologia, 2015)

Mobility and persistence of the herbicide fomesafen in soils cultivated with bean plants using SLE/LTP and HPLC/DAD - Anna I. G. Costa; Maria Eliana L. R. Queiroz; Antônio A. Neves; Roberta C. de Assis; Carlos E. S. dos Soares; Antônio A. da Silva; Leonardo D’Antonino; André F. de Oliveira; Carlos R. Bellato (Environmental Science and Pollution Research, 2015)

Ubiquitin–Proteasome System Impairment and MPTP-Induced Oxidative Stress in the Brain of C57BL/6 Wild-type and GSTP Knockout Mice - Andreia Neves Carvalho; Carla Marques; Elsa Rodrigues; Colin J. Henderson; C. Roland Wolf; Paulo Pereira; Maria João Gama (Molecular Neurobiology, 2013)

Glutathione S-Transferase pi Mediates MPTP-Induced c-Jun N-Terminal Kinase Activation in the Nigrostriatal Pathway - Margarida Castro-Caldas; Andreia Neves Carvalho; Elsa Rodrigues; Colin Henderson; C. Roland Wolf; Maria João Gama (Molecular Neurobiology, 2012)

In vitro inhibitory effect of trichostatin A on canine grade 3 mast cell tumor - Marcia Kazumi Nagamine; Daniel S. Sanches; Katia C. Pinello; Luciana Neves Torres; Gregory Mennecier; Andréia O. Latorre; Heidge Fukumasu; Maria Lucia Zaidan Dagli (Veterinary Research Communications, 2011)

Saccharomyces cerevisiae strains from traditional fermentations of Brazilian cachaça: trehalose metabolism, heat and ethanol resistance - Cristina R. Vianna; Carol L. C. Silva; Maria J. Neves; Carlos A. Rosa (Antonie van Leeuwenhoek, 2008)